Формула разности квадратов :
a² - b² = (a - b) * (a + b)
[tex]\displaystyle\bf\\1)\\\\(6a-7)^{2} -(4a-2)^{2} =\Big[6a-7-(4a-2)\Big]\cdot\Big[6a-7+4a-2\Big]=\\\\\\=(6a-7-4a+2)\cdot(10a-9)=(2a-5)\cdot(10a-9)[/tex]
Формула квадрата суммы :
(a + b)² = a² + 2ab + b²
[tex]\displaystyle\bf\\2)\\\\\underbrace{(a+1)(a-1)}_{a^{2} -1}(a^{2} +1)-(9+a^{2} )^{2} =\\\\=(a^{2} -1)(a^{2} +1)-\Big(9^{2}+2 \cdot 9 \cdot a^{2} +(a^{2} )^{2} \Big)=\\\\=(a^{2} )^{2} -1^{2}-81-18a^{2} -a^{4} =a^{4} -1-81-18a^{2} -a^{4} =-(18a^{2} +1)\\\\a=\frac{1}{3} \\\\-(18a^{2} +1)=-\Big[18\cdot\Big(\frac{1}{3} \Big)^{2} +1\Big]=-\Big(18\cdot\frac{1}{9} +1\Big)=-(2+1)=-3[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Формула разности квадратов :
a² - b² = (a - b) * (a + b)
[tex]\displaystyle\bf\\1)\\\\(6a-7)^{2} -(4a-2)^{2} =\Big[6a-7-(4a-2)\Big]\cdot\Big[6a-7+4a-2\Big]=\\\\\\=(6a-7-4a+2)\cdot(10a-9)=(2a-5)\cdot(10a-9)[/tex]
Формула квадрата суммы :
(a + b)² = a² + 2ab + b²
[tex]\displaystyle\bf\\2)\\\\\underbrace{(a+1)(a-1)}_{a^{2} -1}(a^{2} +1)-(9+a^{2} )^{2} =\\\\=(a^{2} -1)(a^{2} +1)-\Big(9^{2}+2 \cdot 9 \cdot a^{2} +(a^{2} )^{2} \Big)=\\\\=(a^{2} )^{2} -1^{2}-81-18a^{2} -a^{4} =a^{4} -1-81-18a^{2} -a^{4} =-(18a^{2} +1)\\\\a=\frac{1}{3} \\\\-(18a^{2} +1)=-\Big[18\cdot\Big(\frac{1}{3} \Big)^{2} +1\Big]=-\Big(18\cdot\frac{1}{9} +1\Big)=-(2+1)=-3[/tex]